Muhassinat Lafziyyah and Their Semantic Rhetorical Implications in the Qur’an and Hadith - Azzahra Emira Sudrajat; Raswan Raswan (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
This study examines the rhetorical functions of muhassinat lafziyyah within the framework of 'ilm al-badi in the Qur’an and Hadith, focusing on how phonetic features construct meaning and reinforce spiritual messages. While traditionally viewed as mere ornamentation, this research explores their functional role beyond linguistic embellishment. Employing a qualitative descriptive-analytical method with a balaghi approach, the study analyzes selected eschatological verses and Hadith texts containing saja (rhyme), jinas (paronomasia), and iqtibas (intertextual quotation). The findings reveal that these devices function as powerful rhetorical tools that strengthen semantic depth, intensify emotional resonance, and facilitate memorization. For instance, saja in Hadith creates rhythmic harmony that reinforces moral emphasis, while jinis in Ar-Rum (55) and Al-Qiyamah (29–30) generates layered meanings and ironic contrasts regarding worldly transience. This study demonstrates that sound patterns (lafz) are inseparable from meaning (ma'na), playing a crucial role in conveying theological and ethical values. Consequently, understanding these rhetorical functions contributes to a more comprehensive appreciation of the spiritual depth in Islamic discourse.